Repair of Diaphyseal Radius and Ulna Fractures Using a Modified Type I External Skeletal Fixator and Ulnar Intramedullary Pin - Renberg, W. C.; Goring, R. L.; Haan, J. J. de (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Modified type I external skeletal fixation of the radius (using a curved connecting bar and unique pin placement) was combined with intramedullary pinning of the ulna to repair eight ipsilateral radius and ulna fractures in dogs. The intramedullary ulnar pin was placed first, aligning the radial fragments, which allowed closed application of the radial fixation. External skeletal fixation was designed to minimize soft tissue trauma and achieve a uniform boneto- connecting-bar distance. Seven of eight fractures healed in eight to twelve weeks with the technique described. The eighth case needed additional fixation following complications associated with the severity of the injury. Results of this study demonstrate that the technique is a suitable alternative for repair of the fracture types included.A modified type I external skeletal fixator and intramedullary pin was successfully used to repair radius and ulna fractures. The technique was developed in order to provide technically simple but rigid stabilization that minimized soft tissue disruption. The technique is described along with the results in a variety of fracture types.
Keywords: Radius-ulna fracture; external skeletal fixation